Efektivitas Konseling Kelompok Pendekatan Rational Emotive Behavior Therapy Untuk Meningkatkan Self-Disclosure Pada Siswa Terisolir - Syarifah Salwaa; Imas Kania Rahman; Noneng Siti Rosidah (Program Studi Bimbingan Konseling Islam, Fakultas Tarbiyah Dan Ilmu Keguruan, Institut Ummul Quro Al-Islami Bogor, 2026)
Isolated students generally have difficulty adjusting to their social environment and building good relationships with their peers. This situation can hinder students’ ability to engage in self-disclosure with others. This study aims to measure the effectiveness of group counseling services using the Rational Emotive Behavior Therapy (REBT) approach in improving self-disclosure among isolated eighth-grade students at SMP Daar En Nisa Islamic School in Bogor. The research method used was a quasi-experimental design with a time-series design. The study population consisted of 73 eighth-grade students at SMP Daar En Nisa Islamic School in Bogor. The sample was determined based on sociometric results and the characteristics of the group counseling implementation, resulting in five students forming the experimental group who received the treatment in the form of group counseling services using the REBT approach. The results showed that the overall average pretest score for the experimental group was 46.95, while the overall average posttest score for the experimental group was 49.30. The results of the paired-sample t-test showed a Sig. (2-tailed) value of 0.319 (p > 0.05), indicating that there was no significant difference between the pretest and posttest scores in the experimental group. Furthermore, the N-Gain test yielded a mean value of 8.3813%, indicating that group counseling using the REBT approach was not effective in increasing self-disclosure among isolated students.